Addressing the best treatment for non-clear cell renal cell carcinoma: A meta-analysis of randomised clinical trials comparing VEGFR-TKis versus mTORi-targeted therapies. (September 2017) - Ciccarese, Chiara; Iacovelli, Roberto; Brunelli, Matteo; Massari, Francesco; Bimbatti, Davide; Fantinel, Emanuela; De Marco, Vincenzo; Porcaro, Antonio Benito; Martignoni, Guido; Artibani, Walter; Tortora, Giampaolo
Abstract: Aim: Non-clear cell renal cell carcinoma (nccRCC) tumours include a heterogeneous group of malignancies that profoundly differ in terms of morphology, genetic profile, clinical behaviour and prognosis. The optimal treatment algorithm for nccRCC is still unknown and derived mainly from evidence available for ccRCC, being therefore represented by targeted agents against vascular endothelial growth factor and mammalian target of rapamycin (mTOR) pathways. We aimed to compare the efficacy of vascular endothelial growth factor receptor tyrosine kinase inhibitors (VEGFR-TKis) and mTOR inhibitors (mTORi) for the treatment of nccRCC patients. Methods: Searching the MEDLINE/PubMed, Cochrane Library and American Society of Clinical Oncology Meeting abstracts prospective studies were identified. Data extraction was conduced according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. The measured outcomes were progression-free survival (PFS), overall survival (OS) and the overall response rate (ORR). Results: Four randomised controlled trials were selected for final analysis, with a total of 332 patients evaluable for PFS. Treatment with TKi significantly reduced the risk of progression compared with mTORi (hazard ratio [HR] = 0.71; 95% confidence interval [CI] 0.60–0.84; p < 0.0001). This difference remained significant when sunitinib was compared with everolimus in first-line setting (HR = 0.67; 95% CI, 0.56–0.80; p < 0.00001). In the 332 patients evaluable for OS, no significant difference was found between TKi and mTORi (HR = 0.86; 95% CI, 0.67–1.12; p = 0.27). In the 176 evaluable patients, TKis therapy did not improve the ORR when compared with mTORi (relative risk [RR] = 2.21; 95% CI, 0.87–5.60; p = 0.09), even if treatment with sunitinib doubled the probability of achieving a tumour response. Conclusions: Treatment with TKis significantly improves PFS, but not OS, when compared with mTORi. Moreover, sunitinib as first-line therapy reduces the risk of progression compared with everolimus; therefore, supporting the standard treatment paradigm broadly used for ccRCC patients. The relatively modest efficacy of available targeted therapies reinforces the need of future histology based, molecular driven therapeutic paradigm. Highlights: The efficacy of vascular endothelial growth factor receptor tyrosine kinase inhibitors (TKis) and mammalian target of rapamycin inhibitor (mTORi) for the treatment of non-clear cell renal cell carcinoma was compared. TKis significantly improved progression-free survival, but not overall survival, compared with mTORi. First-line sunitinib reduced the risk of progression compared to everolimus. Treatment with TKis did not improve the overall response rate when compared with mTORi.